Ross Errilly Franciscan Friary, west exerior wall, door, jamb, arch and hood - O'Donovan, Danielle (My University, 2008)
West door, moulding from intrados comprises: hollow chamfer, quadrant, hollow chamfer. The hood from extrados in comprises: frontal fillet, hollow chamfer, hollow chamfer. The jamb and arch moulding here is particularly close to that at Tuam, in the south door of the fourteenth-century choir. Although the hood mouldings are different, the manner in which the hoods terminate is very similar.
Door
Keywords: quadrant; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Gothic doorways; Late Medieval; roll moldings; moldings, hollow; hood moldings